Tailoring the Structural Properties of PVDF and P(VDF-TrFE) by Using Natural Polymers as Additives - Simoes, R. D. [UNESP]; Rodriguez-Perez, M. A.; De Saja, J. A.; Constantino, C. J. L. [UNESP] (John Wiley & Sons Inc, 2009)
The poly(vinylidene fluoride), PVDF, and its copolymer poly(vinylidene fluoride-trifluoroethylene), P(VDF-TrFE), are of great scientific and technological interest due to their ferro, pyro, and piezelectrical properties besides chemical and thermal stability. Recently, their biocompatibility has been shown as well. Therefore, considering all this potentiality, self-standing films of PVDF and P(VDF-TrFE) containing corn starch and latex of natural rubber as additives were produced by compressing/annealing forming blends. This process allows one to discard the necessity of using solvents to dissolve either PVDF or P(VDF-TrFE), which are toxic to human. The films were structurally characterized through Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction, density, melt flow index, hardness, and thermal conductivity. The results showed that the polymers do not interact chemically with the additives leading to the formation of blends as physical mixtures where the additives are well dispersed within the blends at micrometer level. However, it was observed that the adhesion of the starch is better in the case of blends with P(VDF-TrFE). Besides, the crystalline structures of the alpha-PVDF and ferroelectric P(VDF-TrFE) are kept in the blends. The density, hardness, melt flow index, and thermal conductivity values of the blends followed what should be expected from physical mixtures. POLYM. ENG. SCL, 49:2150-2157, 2009. (C) 2009 Society of Plastics Engineers